The nymph of Tortopus harrisi Traver (Ephemeroptera: Polymitarcyidae) - Molineri, Carlos; Siegloch, Ana E.; Righi-Cavallaro, Karina O. (Zootaxa, 2010)
Polymitarcyidae is a family of burrowing mayflies (Ephemeroptera: Ephemeroidea) distributed throughout the world but with highest diversity in the Neotropics. Tortopus Needham & Murphy, with a Panamerican distribution, is known from twelve species described in the adult stage. Nymphs are only known for three species: T. puella (Pictet), T. obscuripennis Domínguez and T. sarae Domínguez, and present a rather homogeneous morphology (Molineri 2008). They were firstly described for T. puella by Scott et al. (1959) and later Molineri (2008) described the other two. Both studies reported that these species burrow U-shaped tunnels in clay banks of rivers and streams, thus preventing them from being sampled in most limnological studies (that use surbers, drags, or drift nets).